2020
DOI: 10.3389/fpls.2020.00445
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Considerations for Genetically Modified RNAi Plants: EFSA’s Activities and Perspective

Abstract: Genetically modified plants (GMPs) intended for market release can be designed to induce "gene silencing" through RNA interference (RNAi). The European Food Safety Authority (EFSA) and other international risk assessment bodies/regulatory agencies have taken several actions to determine whether the existing risk assessment approaches for GMPs are appropriate for the risk assessment of RNAi-based GMPs or require complementary or alternative approaches. To our knowledge, at the international level, no dedicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…This study adds to the conclusions from prior research on various insects that these effects tend to be mediated by high dsRNA concentrations [3,5,25], and it also demonstrates that dsRNA formulations can have significant antifeedant effects for orallydelivered RNAi. Second, there is a need to extend research on the relationship between the number of matching siRNA sequences and RNAi efficacy of dsRNA molecules [16,61,62], so that effective dsRNAs can be designed against single or closely-related pest species that vary in sequence identity with the target gene. Attention to these issues will facilitate the development and deployment of RNAi-based solutions for the management of plant sap-feeding and other insect pests.…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to the conclusions from prior research on various insects that these effects tend to be mediated by high dsRNA concentrations [3,5,25], and it also demonstrates that dsRNA formulations can have significant antifeedant effects for orallydelivered RNAi. Second, there is a need to extend research on the relationship between the number of matching siRNA sequences and RNAi efficacy of dsRNA molecules [16,61,62], so that effective dsRNAs can be designed against single or closely-related pest species that vary in sequence identity with the target gene. Attention to these issues will facilitate the development and deployment of RNAi-based solutions for the management of plant sap-feeding and other insect pests.…”
Section: Discussionmentioning
confidence: 99%
“…Since RNAi is a sequence-based mechanism, any dsRNA with sufficient homology to an arthropod mRNA may trigger RNAi in a non-targeted manner. Therefore, dsRNA-mediated approaches under development should be accompanied with ecotoxicological studies to identify any effects in non-target organisms [27][28][29][30]. Castellanos et al [31] reported that the combined use of RNAi-mediated gene silencing against the Neotropical brown stink bug Euschistus heros (F.) (Hemiptera, Pentatomidae), together with eggs of the parasitoid Telenomus podisi Ashmead (Hymenoptera, Scelionidae), proved to be a feasible approach.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the scientific arguments provided in TB-134 does not provide sufficient justification to support the re-examination of the EFSA GMO Panel conclusions Papadopoulou et al (2020) and summarised in EFSA (2020a). To EFSA's knowledge, at the international level, no dedicated guidelines have been developed for the risk assessment and regulation of RNAi-based GMPs, confirming that existing science-based risk assessment approaches for GMPs are generally considered also suitable for RNAi-based GMPs.…”
Section: Efsa Conclusion On Tb-134mentioning
confidence: 93%